TikTok sebagai Media dalam Membentuk Opini Publik melalui Film Netflix Ice Cold - Michel Adriana; Sinta Paramita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The 2016 cyanide coffee murder case was widely discussed in the mass media at the time, with Jessica Wongso as a suspect in the murder of Mirna. This case was brought up again in 2023 through a documentary film entitled